Post-Soviet structures, path-dependency and passivity in Chukotkan coastal villages - Nielsen, Bent (Études/Inuit/Studies, 2007)
AbstractBased on examples from Chukotka’s history, this article focuses on a comparison between the early Soviet period and the years following the dissolution of the Soviet Union, in order to analyse points of distinction and surprising similarities between the two periods. This article compares the events of the two periods and uses the concept of “path-dependency” as an analytical tool to explain the discrepancy between statements of democracy/market-economy and the continued Soviet way of thinking in order to examine the widespread state of powerlessness and passivity among Chukotka’s Indigenous population and the inertia of progression in the bureaucratic system. The article also highlights the importance of the Indigenous elite. In the early years of the Soviet era, the elite underwent suppression and subjugation, which among other things led to an incipient powerlessness and passivity among the Indigenous people in Chukotka. During the past few decades, new up-coming Eskimo (Yupik) and Chukchi elites have begun to launch a number of embryonic initiatives with a non-Soviet origin.